Kesetaraan Gender pada Film Serial Netflix Gadis Kretek - Ramadhan Putranto; Dyva Claretta (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The issue of gender gap and male dominance, which has historically affected the role of women in society, is a common problem. This study aims to examine the representation of gender equality in the Netflix series "Kretek Girl" using a qualitative-descriptive approach with John Fiske's semiotic method using three levels of analysis, namely the reality level, the representation level, and the ideological level. The type of data source was obtained using 2 types, namely primary data in the form of images of Scene clips in the Netflix series "Kretek Girl" and secondary data using literature and literature studies. At the reality level, the series depicts the division of gender roles through visuals and social interactions. At the level of representation, the storyline and cinematographic techniques highlight women's struggles against patriarchal norms. Meanwhile, at the ideological level, the series invites the audience to question the traditional values that limit the role of women. This study emphasizes the importance of understanding the influence of patriarchy in social and cultural contexts, and highlights the relevance of gender equality issues in Indonesia's industry and society